An integrated metabolomics and 16S rRNA gene sequencing approach exploring the molecular pathways and potential targets behind the effects of Radix Scrophulariae. Issue 57 (17th October 2019) - Lu, Fang; Zhang, Ning; Yu, Donghua; Zhao, Hongwei; Pang, Mu; Fan, Yue; Liu, Shumin
Abstract : An integrated approach to assess impact of caecal microbiota on faecal metabolic phenotypes in the presence of Radix Scrophulariae involving 16S rRNA gene sequencing combined with UHPLC/TOF-MS-based faecal metabolomics was applied to Radix Scrophulariae-treated rats. Abstract : To assess the impact of the caecal microbiota on faecal metabolic phenotypes in the presence of Radix Scrophulariae (Chinese name: Xuanshen ), an integrated approach involving 16S rRNA gene sequencing combined with ultrahigh-performance liquid chromatography/time-of-flight mass spectrometry (UHPLC/TOF-MS)-based faecal metabolomics was applied to Radix Scrophulariae-treated rats. Interestingly, Radix Scrophulariae led to significant gut microbiota changes at the phylum and genus levels in treated rats compared to control rats. Additionally, distinct changes in faecal metabolites, including linoleic acid (LA), guanosine, inosine, hypoxanthine, xanthine, 4-hydroxycinnamic acid, cholic acid, N -acetyl-d -glucosamine, l -urobilinogen and uridine, were observed in Radix Scrophulariae-treated rats. Of these, seven metabolites were up-regulated, and the remaining three metabolites were down-regulated. Moreover, there were substantial associations between altered levels of gut microbiota genera and discrepant levels of faecal metabolites, particularly for compounds involved in LA and purine metabolism. These results demonstrated that the gut microbiota is altered in association with faecal metabolism following treatment with Radix Scrophulariae. Our findings suggest that further application of this 16S rRNA gene sequencing and UHPLC/TOF-MS-based metabolomics approach will facilitate the assessment of the pharmacological action of Radix Scrophulariae and thus expand the scope of this herb.